Outcome of Achilles Tendon Repair using Four Strand Cross Locked Cruciate Repair Technique - Dhoju, D.; Thapa, J. (Kathmandu University Medical Journal, 2021)
Background Four strand cross locked cruciate tendon repair technique for Achilles tendon rupture has shown promising result. Objective To evaluate the outcome of all acute traumatic Achilles tendon rupture case treated by a novel repair technique of four strand cross locked cruciate. Method A total of 40 cases of acute traumatic Achilles tendon rupture from 2011 to 2018 treated by four strand cross locked cruciate repair technique were retrospectively evaluated using Achilles Tendon Total Rupture Score. Result Average age of patient was 29.45 years. Male preponderance was seen. Most of the patient (97.5%) had complete rupture of Achilles tendon. Most of the patient (92.5%) had open injury. The average length of hospitalization was 7 days. All the patients recovered to the level of physical activity previous to the tendon lesion. The achilles tendon total rupture score significantly improved from 6 month post op period to 12 months (p=0.02) and 2 years post op period (p=0.038). Conclusion The optimum method of suturing technique for acute traumatic rupture of Achilles tendon remains controversial. The four strand cross locked cruciate repair technique provides a stable and reliable construct for the Achilles tendon repair. The technique requires further investigation with direct comparison with other mostly used techniques like Krackow and Gift box suture technique.